Nilai-Nilai Kearifan Lokal Tradisi Sedekah Bumi - Dudi Badruzaman; Qomar Abdurrahman (Jurnal Inovasi Komunikasi, 2024)
Local wisdom in an era of modernisation and digitalisation demands social change in a region's society. The tradition of sedekah bumi (earth alms) is a medium for internalising local wisdom values, which are currently beginning to shift in line with the development of the digital world, the effects of which are strongly felt in society. This paper aims to describe the Islamic values and local wisdom of the community in the tradition of sedekah bumi in Sirnabaya Village, Rajadesa District, Ciamis Regency, West Java. The research method used a phenomenological approach conducted in Sirnabaya Village, Rajadesa District, Ciamis Regency, West Java, with research subjects consisting of the village head, religious leaders, traditional leaders, and the community in Sirnabaya Village. Data collection was carried out through interviews, observations, and various documentation studies. Data validity was tested using source triangulation. The data was analysed using the Social Construction Theory of Peter L. Berger and Thomas Luckman. The results of the study show that the tradition of sedekah bumi in Cikedung Village is still maintained with a spirit of mutual cooperation in accordance with social construction theory, which emphasises a simultaneous three-moment approach, namely internalisation, objectification, and externalisation. The process of internalising these local wisdom values involves cultural and Islamic acculturation.